Политика Идентичности и Демократия В Индонезии (Identity Politics and Democracy In Indonesia) - Setiawan, Refly; Valentinovna , Kolesova Olga (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
The article presents an analysis of the implementation of identity policy in Indonesia in its correlation with the democratic principles proclaimed by the government. The importance of having a state identity in the modern political situation is substantiated. An understanding of identity is provided from a scientific perspective, and the specifics of understanding identity in Indonesian national policy are explored. The reliance on understanding identity is based on national specifics, including traditions, state laws, symbols, and the constitution that prescribe its interpretation. The connection between identity policy and the proclaimed democracy is shown. An assumption is made about the potential for further identity formation in the country. The specifics of how the Indonesian government interprets democratic principles are highlighted. The main principles of democracy are given -